Update of Immunosenescence in Cerebral Small Vessel Disease - Jian, Banghao; Hu, Mengyan; Cai, Wei; Zhang, Bingjun; Lu, Zhengqi (Frontiers in Immunology, 2020)
Aging of the central nervous system (CNS) is closely associated with chronic sterile low-grade inflammation in older organisms and related immune response. As an amplifier for neuro-inflammaging, immunosenescence remodels and deteriorates immune systems gradually with the passage of time, and finally contributes to severe outcomes like stroke, dementia and neurodegeneration in elderly adults. Cerebral small vessel disease (CSVD), one of the major causes of vascular dementia, has an intensive connection with the inflammatory response and immunosenescence plays a crucial role in the pathology of this disorder. In this review, we discuss the impact of immunosenescence on the development of CSVD and its underlying mechanism. Furthermore, the clinical practice significance of immunosenescence management and the diagnosis and treatment of CSVD will be also discussed.